A method for preparing 1,6-hexanediamine
By using a non-uniform catalyst to carry out the 1,6-hexanediol amination reaction under a hydrogen atmosphere, the problems of high selectivity of oligomers and harsh reaction conditions in the prior art were solved, and efficient and environmentally friendly 1,6-hexanediamine preparation was achieved, which improved yield and catalyst life.
Patent Information
- Application Number
- CN202111419455.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-11-26
AI Technical Summary
The existing 1,6-hexanediol synthesis process has problems such as high oligomer selectivity, inability to continuously produce, harsh reaction conditions, low conversion of 1,6-hexanediol, and low selectivity of hexanediamine.
A non-uniform catalyst is used, and the catalyst particles are composed of a core and an outer layer. The inner core and outer layer are composed of active metals, additives and carriers. The non-uniform catalyst is synthesized by a two-step method for the amination reaction of 1,6-hexanediol under a hydrogen atmosphere.
It has achieved the advantages of reducing oligomer generation, increasing the yield of 1,6-hexanediamine, extending the life of the catalyst, and simplifying the reaction conditions. It has the advantages of green and clean, good atomic economy, environmental protection and low energy consumption.
Smart Images

Figure BDA0003376696050000211 
Figure BDA0003376696050000221
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of fine chemical products, and in particular to a method for preparing 1,6-hexanediamine by using 1,6-hexanediol as a raw material, and in detail to a method for converting 1,6-hexanediol and ammonia into 1,6-hexanediamine under a non-uniform catalyst and a hydrogen atmosphere, while achieving the effects of reducing the generation of oligomers, increasing the yield of 1,6-hexanediamine, and increasing the life of the catalyst. Background Art
[0002] 1,6-Hexanediamine (i.e. hexamethylenediamine) is the main raw material for the production of polyhexamethylene adipamide (nylon 66), hexamethylene isocyanate, synthetic resin, organic crosslinking agent and other materials. The common production processes of 1,6-hexanediamine mainly include: butadiene hydrocyanation and 1,6-adiponitrile hydrogenation method, 1,6-hexanediol or 6-amino-1-hexanol amination method, caprolactam method, 1,6-hexanedialdehyde reduction amination method, etc. At present, the synthesis of hexamethylenediamine by butadiene method is the mainstream process in the industry, but the core technology is monopolized by foreign chemical companies, and my country's 1,6-adiponitrile raw materials are almost completely dependent on imports. In addition, the hydrocyanic acid used in the butadiene method is highly toxic and the process route is complicated, which does not meet the needs of contemporary green chemical industry.
[0003] Compared with other process routes, the 1,6-hexanediol method for synthesizing hexamethylenediamine has the advantages of being green and clean, having good atom economy, being environmentally friendly, and having low energy consumption, and has long been widely concerned. In the amination reaction of 1,6-hexanediol, when the conversion rate is too high, in addition to generating the target product hexamethylenediamine, the intermediate product 6-amino-1-hexanol, and the product cyclohexylimine with certain added value, it is also easy to undergo deep reactions to generate by-products such as oligomers, mainly including dimers and trimers of 1,6-hexanediol and hexamethylenediamine. The generation of oligomers causes a waste of raw materials, increases processing costs, and reduces the yield of hexamethylenediamine, thereby weakening the competitive advantage of the 1,6-hexanediol method for synthesizing hexamethylenediamine. Reducing the generation of oligomers is an important prerequisite for realizing the industrial-scale application of the 1,6-hexanediol method for synthesizing hexamethylenediamine.
[0004] U.S. Patent 2754330 reported that Ru / charcoal catalyst was used to synthesize hexamethylenediamine from 1,6-hexanediol and ammonia water. When the reaction was carried out in an intermittent reactor at a temperature of 225-231°C and a pressure of 87.5-94MPa, more by-products were produced in the product. U.S. Patent 3215742 used Raney nickel to catalyze the amination of 1,6-hexanediol to synthesize hexamethylenediamine. The reaction was carried out in an intermittent reactor. After 6 hours of reaction at 200°C and 13.7MPa, the conversion rate was 58% and the selectivity of hexamethylenediamine was 67%. Yan Li et al. used a carrier treated with an ammonia source to synthesize Ni-Cu-B and other system catalysts in Chinese Patent 106807377. After the hydrogen amination reaction of 1,6-hexanediol at 160°C and 8MPa in a fixed bed reactor, the conversion rate was as high as 95%, and the product contained about 3.2% of oligomer components. Yang Dongyuan et al. prepared a eutectic catalyst using a limited ratio of Co-Re-Cu and vitrified silica in Chinese patent 111495383, which was used for the amination of 1,6-hexanediol on a fixed bed, with a conversion rate of 92.5% at 340°C and 1.5 MPa, and a selectivity of 93.6% for hexamethylenediamine. Du Baolei et al. used an alkali-treated carrier-supported Co-Cu-Ru to catalyze the amination of 1,6-hexanediol to hexamethylenediamine in Chinese patent 111151256, with a conversion rate of 79% at 160°C and 7.5 MPa on a fixed bed, and 4.2% of oligomers in the product.
[0005] In summary, the existing technology of synthesizing hexamethylenediamine by 1,6-hexanediol method has one or more problems such as high oligomer selectivity, inability to produce continuously, harsh reaction conditions, low 1,6-hexanediol conversion rate, and low hexamethylenediamine selectivity. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing 1,6-hexanediamine. The method can solve the problems of more by-product oligomers, inability to produce continuously, short catalyst life, low hexanediamine yield, harsh reaction conditions, etc. in the current 1,6-hexanediol method for preparing hexanediamine, and has the advantages of being green and clean, high atom utilization, good catalyst stability, high hexanediamine yield, etc.
[0007] The method for preparing 1,6-hexanediamine is characterized in that 1,6-hexanediol is used as a raw material and subjected to hydroamination under the action of a heterogeneous catalyst to generate the target product 1,6-hexanediamine.
[0008] According to one aspect of the application, a novel reductive amination catalyst for the hydroamination of 1,6-hexanediol to synthesize hexamethylenediamine is provided.
[0009] The novel reductive amination catalyst is characterized in that when used for the hydroamination of 1,6-hexanediol to synthesize hexamethylenediamine, it has the advantages of less oligomerization side reactions, high activity, mild reaction conditions, high hexamethylenediamine yield, long service life, etc.
[0010] The novel reductive amination catalyst is a non-uniform catalyst, the catalyst particles of which consist of an inner core and an outer layer, and are characterized in that the inner core is the inner center part of the catalyst particle, and the outer layer is the part from the inner core of the catalyst particle to the outer surface of the particle.
[0011] The inner core and outer layer of the catalyst particles are both composed of active metals, additives and carriers.
[0012] The active metal and auxiliary agent components are uniformly dispersed on the inner surface of the carrier pores.
[0013] There is a concentration difference between the total active metal loading per unit volume contained in the inner core and the outer layer of the catalyst particles.
[0014] The carrier is one or a combination of granular SiO2 or Al2O3.
[0015] The inner part of the carrier particle is loaded with inner core active metal and auxiliary agent as the inner core of the catalyst, and the outer layer active metal and auxiliary agent are loaded in the area between the outer surface of the carrier particle and the inner core as the outer layer of the catalyst.
[0016] The particle size of the granular carrier is 0.4-50 mm, and the thickness of the outer layer of the heterogeneous catalyst is 0.1-1 mm.
[0017] Preferably, the particle size of the granular carrier is 1.2 to 14 mm, and the thickness of the outer layer of the heterogeneous catalyst is 0.2 to 0.8 mm.
[0018] More preferably, the particle size of the granular carrier is 2.5 to 7.5 mm, and the thickness of the outer layer of the heterogeneous catalyst is 0.3 to 0.6 mm.
[0019] The granular SiO2 or Al2O3 carrier can be in the shape of a column, annulus, sphere, trifoliate, quadrifoliate, amorphous, etc.;
[0020] The specific surface area of the granular SiO2 or Al2O3 carrier is 50 to 2000 m 2 / g, preferably 150-600m 2 / g; pore volume 0.05~2.0ml / g, preferably 0.4~1.2ml / g.
[0021] The granular shaped Al2O3 carrier crystal phase may be pseudo-boehmite, γ-Al2O3, η-Al2O3, κ-Al2O3, χ-Al2O3, θ-Al2O3, α-Al2O3, ρ-Al2O3 or an amorphous phase.
[0022] The volume of the outer layer of the heterogeneous catalyst accounts for 10 to 88% of the total catalyst volume, preferably 30 to 75%, and more preferably 40 to 65%.
[0023] The active metal elements are one or more combinations of Co, Ni, and Cu, wherein the mass of the inner core active metal accounts for 1 to 9% of the mass of the inner core carrier, preferably 1.5 to 7%, and more preferably 2 to 4.5%; the mass of the outer layer active metal accounts for 10 to 95% of the mass of the outer layer carrier, preferably 15 to 60%, and more preferably 25 to 45%.
[0024] The auxiliary agent component is one or more combinations of Ru, Pd, Fe, B, Zn, Re, W, Y, etc., preferably one or more combinations of Ru, Pd, Re, W, etc., wherein the mass ratio of the inner core auxiliary agent to the inner core active metal is 0.01-0.3:1, preferably 0.05-0.2:1; the mass ratio of the outer layer auxiliary agent to the outer layer active metal is 0.05-0.3:1, preferably 0.1-0.2:1.
[0025] The active metal loaded on the inner core is A, and the mass of A loaded per unit volume is M, the auxiliary agent is B, and the mass of B loaded per unit volume is N; the active metal loaded on the outer layer includes A, and the mass of A loaded per unit volume is greater than or equal to M, the auxiliary agent includes B, and the mass of B loaded per unit volume is greater than or equal to N; and the mass of the total active metal loaded per unit volume on the outer layer is greater than the mass of the total active metal loaded per unit volume on the inner core, and the mass of the total auxiliary agents loaded per unit volume on the outer layer is greater than or equal to the mass of the total auxiliary agents loaded per unit volume on the inner core.
[0026] The heterogeneous catalyst can be synthesized by a two-step method.
[0027] The implementation process of Scheme A as a two-step method for synthesizing heterogeneous catalysts can be achieved through the following two steps:
[0028] The first step is to prepare a precursor solution of an active metal or an additive, load the active metal and the additive onto a carrier by an impregnation method or a precipitation method, and obtain a uniform catalyst after drying and calcination, wherein the loading amount of the active metal and the additive on the obtained uniform catalyst is the same as the loading amount required for the inner core of the heterogeneous catalyst;
[0029] In the second step, on the uniform catalyst prepared in the first step, the precursor liquid of active metals and additives is prepared according to the required loading amount of the outer layer, and the active metals and additives are loaded into the outer layer of the uniform catalyst by competitive adsorption method, air bag retardation method or rapid drying method. After drying and calcination, the non-uniform catalyst is finally obtained.
[0030] The two-step method can change the order of the first step and the second step according to actual needs.
[0031] As the implementation process of the two-step method for synthesizing heterogeneous catalysts, the B scheme can also be realized through the following two steps:
[0032] The first step is to prepare the precursor liquid of active metal and additive according to the volume ratio of the outer layer of the heterogeneous catalyst and the difference in the loading amount of active metal and additive in the outer layer and the inner core, and load the active metal and additive to the outer layer of the carrier by competitive adsorption method, air bag retardation method or rapid drying method, and finally obtain the eggshell catalyst after drying and calcination;
[0033] In the second step, on the eggshell catalyst prepared in the first step, a precursor liquid is prepared according to the active metal and additive loading required for the inner core, the active metal and additive are loaded onto the eggshell catalyst by impregnation or precipitation, and a non-uniform catalyst is obtained after drying and calcination.
[0034] Among them, the total active metal loading in the shell layer of the eggshell-type catalyst obtained in the first step is lower than the total active metal loading in the outer layer of the heterogeneous catalyst.
[0035] The calcination temperature is 200-800° C., the time is 0.5-15 hours, and the calcination is carried out in an atmosphere of one or both of air and oxygen.
[0036] Optionally, the impregnation method embodiment includes co-impregnation, multi-step impregnation, equal volume impregnation, excess impregnation, etc.
[0037] The preparation process is explained by the rapid drying method: according to the proportion of the required non-uniform catalyst outer layer to the total catalyst volume, the loading amount of the outer layer active metal and the auxiliary agent, and the water absorption rate of the uniform catalyst or the carrier, the precursor liquid is prepared, and the precursor liquid is dripped onto the uniform catalyst or the carrier, and then dried and calcined to obtain the non-uniform catalyst or eggshell catalyst; wherein, during the process of dripping the precursor liquid, heating, atmosphere purging and stirring are maintained, the dripping time is 0.1 to 2 hours, the heating temperature is 50 to 200°C, the atmosphere can be one or both of air and nitrogen, and the purging air velocity is 100 to 10000h -1 , the stirring speed is 10 to 300 r / min; the volume of the prepared precursor liquid is 1 to 2.2 times the product of the volume proportion of the outer layer of the catalyst and the saturated water absorption of the uniform catalyst or the carrier.
[0038] During the implementation of the rapid drying method, when the concentration of the active metal or auxiliary agent precursor liquid is too high, the loading of the active metal or auxiliary agent can be completed in two or more times.
[0039] During the implementation of the rapid drying method, when the active metal or auxiliary agent is loaded twice or more times, the volume of the precursor liquid prepared each time is 1 to 2.2 times the product of the volume ratio of the outer layer and the saturated water absorption of the uniform catalyst or carrier.
[0040] Optionally, the precursor of the active component includes a soluble salt of Co, a soluble salt of Ni, and a soluble salt of Cu.
[0041] Optionally, the precursor of the auxiliary agent includes a soluble salt of the auxiliary agent elements Ru, Pd, Fe, B, Zn, Re, W, Y, etc.
[0042] According to another aspect of the present application, a process for synthesizing hexamethylenediamine from 1,6-hexanediol via hydroamination over the heterogeneous catalyst is provided, wherein the process has the advantages of a wide source of raw materials, few by-products such as dimers or trimers, continuous production, and a high yield of hexamethylenediamine.
[0043] The hydroamination reaction of 1,6-hexanediol over a heterogeneous catalyst is carried out in a reactor, including a fixed bed, a fluidized bed, a slurry bed, a bubbling bed or a reactor, etc., preferably a fixed bed reactor.
[0044] The reaction raw materials are 1,6-hexanediol and ammonia, wherein the ammonia can be liquid ammonia or aqueous ammonia.
[0045] The reaction raw materials may also be ammonia and 6-amino-1-hexanol, or a mixture of 1,6-hexanediol / 6-amino-1-hexanol (mass ratio 1: 0.01-100), or a mixture of 1,6-hexanediol / 6-amino-1-hexanol / cycloheximide (mass ratio 1: 0.01-100: 0.1-10), or a mixture of 6-amino-1-hexanol / cycloheximide (mass ratio 1: 0.2-8).
[0046] The ratio of the total mole number of 1,6-hexanediol or 6-amino-1-hexanol or cyclohexylimine to the mole number of ammonia in the reaction raw materials is 1:1-60, preferably 1:6-30.
[0047] No additional solvent is needed to be added to the raw materials.
[0048] The hydroamination reaction conditions are as follows: a pressure of 2 to 25 MPa; a reaction temperature of 80 to 240° C.; and a liquid hourly space velocity of the reaction raw materials other than ammonia of 0.05 to 4 h -1 ; The molar fraction of hydrogen is 0.5 to 20% of the total feed, and the total feed includes reaction raw materials and hydrogen.
[0049] Preferably, the pressure is 4-18 MPa; the reaction temperature is 120-180°C; the liquid hourly space velocity of the reaction raw materials other than ammonia is 0.2-1.5 h -1 .
[0050] The heterogeneous catalyst needs to be reduced and activated before treatment. The reduction and activation treatment is carried out in a hydrogen atmosphere. The activation conditions are: temperature 150-700°C, time 0.5-12h, hydrogen space velocity 20-4000h -1 .
[0051] The reducing atmosphere may also be a hydrogen / nitrogen mixture. DETAILED DESCRIPTION
[0052] The present invention will be further described below by means of specific examples.
[0053] In the embodiments and comparative examples, the diameter of the carrier particles is measured by a vernier caliper, and the average value of 50 measurement results is taken; the thickness of the outer layer or shell layer in the non-uniform catalyst or eggshell catalyst in the embodiments and comparative examples is measured by an optical method: the cross-section of the catalyst particles is obtained by a cutting method, and the image is obtained by an optical microscope. The thickness of the outer layer or shell layer is calculated with the catalyst particle diameter as a reference, and the average value of 50 measurement results is taken; the loading amount of active metals and additives in the embodiments and comparative examples is obtained by X-ray fluorescence spectroscopy analysis, and the listed loading amount values are the percentage of the converted active metal or additive in the carrier mass of the outer layer or inner core of the catalyst.
[0054] The measured thickness of the catalyst outer layer or shell layer, the calculated outer layer volume ratio, the calculated (core active metal mass / core carrier mass) percentage, (core additive mass / core carrier mass) percentage, (outer layer active metal mass / outer layer carrier mass) percentage, and (outer layer additive mass / outer layer carrier mass) percentage are all listed in Tables 1 and 2.
[0055] The catalysts prepared in the examples and comparative examples were evaluated for reaction using a fixed bed reactor. To eliminate the effects of tube wall effects and heat transfer on the reaction results on catalysts of different particle sizes, the hydroamination reaction was carried out in reactors with different inner diameters, wherein the ratio of the reactor inner diameter to the catalyst diameter was about 8:1, and the ratio of the catalyst bed height to the reactor inner diameter was 4:1. The reaction temperature was 165°C and the hydrogen pressure was 8.0 MPa. Except for Examples 21 and 22, the raw materials used in the other examples and comparative examples were 1,6-hexanediol and ammonia, and the liquid volume space velocity of 1,6-hexanediol was 0.6 h -1 The molar ratio of ammonia to 1,6-hexanediol to hydrogen in the reaction process is 16:1:0.7. The raw materials used in Example 21 are a mixture of (1,6-hexanediol / 6-amino-1-hexanol) and ammonia, and the liquid volume space velocity of the mixture is 0.6h -1, wherein the mass ratio of 1,6-hexanediol to 6-amino-1-hexanol is 1:0.5, and the molar ratio of ammonia to (1,6-hexanediol / 6-amino-1-hexanol) to hydrogen in the reaction process is 16:1:0.7. The raw materials used in Example 22 are a mixture of (1,6-hexanediol / 6-amino-1-hexanol / cyclohexylimine) and ammonia, and the liquid volume space velocity of the mixture is 0.6h -1 , wherein the mass ratio of 1,6-hexanediol:6-amino-1-hexanol:cyclohexyl imine is 1:0.5:0.6, and the molar ratio of ammonia to (1,6-hexanediol / 6-amino-1-hexanol / cyclohexyl imine) to hydrogen in the reaction process is 16:1:0.7. Sampling and analysis were performed using an Agilent 7890 gas chromatograph, the chromatographic column was an HP-5 capillary column, and the detector was a hydrogen flame detector. n-Butanol was used as an internal standard for quantitative analysis. The reaction evaluation time and reaction results are listed in Tables 1 and 2.
[0056] Example 1
[0057] Catalyst 1 is a non-uniform 15Ni10Co3.75Re / 2Ni1Co0.3Re-Al2O3. Step 1: Weigh 100g of an average particle size of 1.5mm and a specific surface area of 340m 2 / g, pore volume 0.5ml / g Al2O3 beads were used as carriers, 80ml of aqueous solution containing 9.91g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, and 0.43g NH4ReO4 was prepared, and the Al2O3 carrier was impregnated with the aqueous solution, dried naturally, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 500℃ for 5 hours to obtain a uniform 2Ni1Co0.3Re-Al 2O3 sample; Step 2: Take the uniform 2Ni1Co0.3Re-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.75 ml. Prepare 80 ml of an aqueous solution containing 32.2 g of Ni(NO3)2·6H2O, 22.22 g of Co(NO3)2·6H2O, and 2.48 g of NH4ReO4. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 2000 h -1 The precursor solution was added to the 2Ni1Co0.3Re-Al2O3 sample at a rate of 3.5 ml / min under the conditions of purging and stirring at 40 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 5 hours. Finally, the heterogeneous 15Ni10Co3.75Re / 2Ni1Co0.3Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400°C for 800 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0058] Example 2
[0059] Catalyst 2 is a non-uniform 25Ni3.75Ru / 3Ni0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 2.4 mm and a specific surface area of 400 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 110ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 500℃ for 5 hours to obtain a uniform 3Ni0.3Ru-SiO2 sample; Step 2: Take the uniform 3Ni0.3Ru-SiO2 sample prepared in the first step, measure the water absorption per gram of sample to be 1ml, prepare 60ml of aqueous solution containing 54.50g Ni(NO3)2·6H2O, 4.66g RuCl3·3H2O, heat at 100℃, nitrogen for 2500h -1 The precursor solution was added to the 3Ni0.3Ru-SiO2 sample at a rate of 4 ml / min under the conditions of purging and stirring at 45 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 400°C for 5 hours to obtain a non-uniform 25Ni3.75Ru / 3Ni0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 350°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0060] Example 3
[0061] Catalyst 3 is a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2. Step 1: Weigh 100 g of 25Co3.75Ru / 3Co0.3Ru-SiO2 with an average particle size of 3.4 mm and a specific surface area of 420 m 2 / g, pore volume 0.6ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ru-SiO2 sample; Step 2: Take the uniform 3Co0.3Ru-SiO2 sample prepared in the first step, measure the water absorption per gram of sample to be 1.1ml, prepare 70ml of aqueous solution containing 59.76g Co(NO3)2·6H2O, 5.13g RuCl3·3H2O, heat at 100℃, nitrogen for 2500h -1The precursor solution was added to the 3Co0.3Ru-SiO2 sample at a rate of 3.5 ml / min under the conditions of purging and stirring at 35 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0062] Example 4
[0063] Catalyst 4 is a non-uniform 20Co5Cu3.75Re / 3Co0.3Re-Al2O3. Step 1: Weigh 100 g of 20Co5Cu3.75Re / 3Co0.3Re-Al2O3 with an average particle size of 6.0 mm and a specific surface area of 380 m 2 / g, pore volume 0.4ml / g Al2O3 beads as carrier, prepare 75ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.43g NH4ReO4, use this aqueous solution to impregnate the above Al2O3 carrier, dry naturally, treat in an oven at 100℃ for 4 hours, and calcine in a muffle furnace at 450℃ for 5 hours to obtain a uniform 3Co0.3Re-Al2O3 sample; Step 2: Take the uniform 3Co0.3Re-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.65ml, prepare 77ml of aqueous solution containing 46.18g Co(NO3)2·6H2O, 8.12g Cu(NO3)3, and 2.73g NH4ReO4, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 2000h -1 The precursor solution was added to the 3Co0.3Re-Al2O3 sample at a rate of 3.8 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 5 hours. Finally, the heterogeneous 20Co5Cu3.75Re / 3Co0.3Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 320°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0064] Example 5
[0065] Catalyst 5 is a non-uniform 25Ni3.75Re / 3Ni0.3Re-Al2O3. Step 1: Weigh 100 g of 25Ni3.75Re / 3Ni0.3Re-Al2O3 with an average particle size of 7.7 mm and a specific surface area of 360 m 2 / g, pore volume 0.4ml / g Al2O3 beads as the carrier, prepare 72ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 0.43g NH4ReO4, use the aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 100℃ for 4 hours, and roast it in a muffle furnace at 500℃ for 5 hours to obtain a uniform 3Ni0.3Re-Al2O3 sample; Step 2: Take the uniform 3Ni0.3Re-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of the sample to be 0.6ml, prepare 75ml of aqueous solution containing 59.95g Ni(NO3)2·6H2O, 2.73g NH4ReO4, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 85℃, nitrogen for 2000h -1 The precursor solution was added to the 3Ni0.3Re-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 110°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 25Ni3.75Re / 3Ni0.3Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0066] Example 6
[0067] Catalyst 6 is a non-uniform 30Ni3Ru1.5B / 4.5Ni0.25Ru0.2B-SiO2. Step 1: Weigh 100g of an average particle size of 9.6mm and a specific surface area of 460m 2 / g, 0.5ml / g pore volume of SiO2 beads as the carrier, prepare 95ml of aqueous solution containing 22.30g Ni(NO3)2·6H2O, 0.68g RuCl3·3H2O, 1.15g H3BO3, impregnate the above SiO2 carrier with this aqueous solution, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain uniform 4.5Ni0.25Ru0.2B-Si O2 sample; Step 2: Take the uniform 4.5Ni0.25Ru0.2B-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.8 ml. Prepare 65 ml of an aqueous solution containing 40.45 g Ni(NO3)2·6H2O, 1.71 g RuCl3·3H2O, and 1.71 g H3BO3, divide the precursor liquid into three equal parts, and repeat the following process three times: heat at 110°C, nitrogen for 2000 h -1The precursor solution was added to the 4.5Ni0.25Ru0.2B-SiO2 sample at a rate of 2ml / min under the conditions of purging and stirring at 30r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 500℃ for 4 hours. Finally, a non-uniform 30Ni3Ru1.5B / 4.5Ni0.25Ru0.2B-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400℃ for 500h. -1 The space velocity reduction activation was carried out for 4 hours.
[0068] Example 7
[0069] Catalyst 7 is a non-uniform 25Ni5Cu4.5Pd / 3.5Ni1Cu0.45Pd-Al2O3. Step 1: Weigh 100g of an average particle size of 6.0mm and a specific surface area of 400m 2 / g, 0.4ml / g pore volume of Al2O3 beads as the carrier, prepared 80ml of aqueous solution containing 17.34g Ni(NO3)2·6H2O, 2.95g Cu(NO3)3, 1.10g Pd(NO3)2·2H2O, impregnated the Al2O3 carrier with the aqueous solution, dried naturally, treated in an oven at 100℃ for 4 hours, and calcined in a muffle furnace at 500℃ for 5 hours to obtain a uniform 3.5Ni1Cu0.45Pd-Al2O3. 2O3 sample; Step 2: Take the uniform 3.5Ni1Cu0.45Pd-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.65 ml. Prepare 78 ml of aqueous solution containing 37.28 g Ni(NO3)2·6H2O, 4.13 g Cu(NO3)3, and 3.45 g Pd(NO3)2·2H2O, divide the precursor solution into three equal parts, and repeat the following process three times: heat at 95°C and nitrogen for 1500 h -1 The precursor solution was added to the 3.5Ni1Cu0.45Pd-Al2O3 sample at a rate of 2.2ml / min under the conditions of purging and stirring at 35r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 450℃ for 4 hours. Finally, a non-uniform 25Ni5Cu4.5Pd / 3.5Ni1Cu0.45Pd-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420℃ for 800h. -1 The space velocity reduction activation was carried out for 4 hours.
[0070] Example 8
[0071] Catalyst 8 is a non-uniform 30Co3Pd1.5Re / 4.5Co0.25Pd0.2Re-SiO2. Step 1: Weigh 100g of 3.9mm average particle size and 420m2 specific surface area. 2 / g, 0.5ml / g pore volume of SiO2 beads as the carrier, prepared 100ml of aqueous solution containing 22.22g Co(NO3)2·6H2O, 0.61g Pd(NO3)2·2H2O, 0.29g NH4ReO4, the aqueous solution was used to impregnate the above SiO2 carrier, naturally dried, treated in an oven at 110℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 4.5Co0.25Pd0.2Re-S iO2 sample; Step 2: Take the uniform 4.5Co0.25Pd0.2Re-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.85ml. Prepare 90ml of aqueous solution containing 63.17g Co(NO3)2·6H2O, 3.35g Pd(NO3)2·2H2O, and 0.94g NH4ReO4, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 1500h -1 The precursor solution was added to the 4.5Co0.25Pd0.2Re-SiO2 sample at a rate of 5ml / min under the conditions of purging and stirring at 40r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 450℃ for 4 hours. Finally, the heterogeneous 30Co3Pd1.5Re / 4.5Co0.25Pd0.2Re-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 350℃ for 600h. -1 The space velocity reduction activation was carried out for 4 hours.
[0072] Example 9
[0073] Catalyst 9 is a non-uniform 20Ni10Co4.5Ru / 2.5Ni2Co0.45Ru-Al2O3. Step 1: Weigh 100g of an average particle size of 2.3mm and a specific surface area of 435m 2 / g, 0.4ml / g pore volume of Al2O3 beads as the carrier, prepared 80ml of aqueous solution containing 12.39g Ni(NO3)2·6H2O, 9.88g Co(NO3)2·6H2O, 1.22g RuCl3·3H2O, the aqueous solution was used to impregnate the above Al2O3 carrier, dried naturally, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 2.5Ni2Co0.45Ru-Al 2O3 sample; Step 2: Take the uniform 2.5Ni2Co0.45Ru-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.7 ml. Prepare 110 ml of an aqueous solution containing 62.43 g of Ni(NO3)2·6H2O, 28.45 g of Co(NO3)2·6H2O, and 7.88 g of RuCl3·3H2O. Divide the precursor solution into two equal parts, and repeat the following process twice: heat at 95°C and nitrogen for 1500 h -1The precursor solution was added to the 2.5Ni2Co0.45Ru-Al2O3 sample at a rate of 6ml / min under the conditions of purging and stirring at 30r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 400℃ for 4 hours. Finally, a non-uniform 20Ni10Co4.5Ru / 2.5Ni2Co0.45Ru-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 350℃ for 600h. -1 The space velocity reduction activation was carried out for 4 hours.
[0074] Example 10
[0075] Catalyst 10 is a non-uniform 20Ni10Co4.5Ru / 4.5Ni0.45Ru-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 1.9 mm and a specific surface area of 440 m 2 / g, pore volume 0.4ml / g Al2O3 beads as carrier, prepare 82ml of aqueous solution containing 22.30g Ni(NO3)2·6H2O, 1.22g RuCl3·3H2O, use this aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and roast it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 4.5Ni0.45Ru-Al2O3 sample; Step 2: Take the uniform 4.5Ni0.45Ru-Al2O3 sample prepared in the first step, measure the water absorption of each gram of sample to be 0.7ml, prepare 120ml of aqueous solution containing 61.44g Ni(NO3)2·6H2O, 39.51g Co(NO3)2·6H2O, 8.76g RuCl3·3H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 1800h -1 The precursor solution was added to the 4.5Ni0.45Ru-Al2O3 sample at a rate of 7.2 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 450°C for 4 hours. Finally, a non-uniform 20Ni10Co4.5Ru / 4.5Ni0.45Ru-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 500°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0076] Embodiment 11
[0077] Catalyst 11 is a non-uniform 25Co2Re1B / 1.2Co0.12B-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 5.93g Co(NO3)2·6H2O, 0.69g H3BO3, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 1.2Co0.12B-SiO2 sample; Step 2: Take the uniform 1.2Co0.12B-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 1.1ml, prepare 130ml of aqueous solution containing 64.65g Co(NO3)2·6H2O, 1.58g NH4ReO4, and 2.77g H3BO3, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 100℃, nitrogen for 2000h -1 The precursor solution was added to the 1.2Co0.12B-SiO2 sample at a rate of 7ml / min under the conditions of purging and stirring at 40r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 450℃ for 4 hours. Finally, a non-uniform 25Co2Re1B / 1.2Co0.12B-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 350℃ for 500h. -1 The space velocity reduction activation was carried out for 4 hours.
[0078] Example 12
[0079] Catalyst 12 is a non-uniform 20Ni5Cu3Pd / 1.8Ni0.18Pd-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 8.92g Ni(NO3)2·6H2O, 0.44g Pd(NO3)2·2H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 1.8Ni0.18Pd-SiO2 sample; Step 2: Take the uniform 1.8Ni0.18Pd-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 1.1ml, prepare 130ml of aqueous solution containing 49.60g Ni(NO3)2·6H2O, 8.12g Cu(NO3)2, and 3.78g Pd(NO3)2·2H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 100℃, nitrogen for 2000h -1The precursor solution was added to the 1.8Ni0.18Pd-SiO2 sample at a rate of 7ml / min under the conditions of purging and stirring at 40r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 450℃ for 4 hours. Finally, a non-uniform 20Ni5Cu3Pd / 1.8Ni0.18Pd-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400℃ for 500h. -1 The space velocity reduction activation was carried out for 4 hours.
[0080] Embodiment 13
[0081] Catalyst 13 is a non-uniform 20Ni5Cu3Pd / 4Ni0.4Pd-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 19.82g Ni(NO3)2·6H2O, 0.98g Pd(NO3)2·2H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 4Ni0.4Pd-SiO2 sample; Step 2: Take the uniform 4Ni0.4Pd-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 1.1ml, prepare 130ml of aqueous solution containing 43.60g Ni(NO3)2·6H2O, 8.12g Cu(NO3)2, and 3.49g Pd(NO3)2·2H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 100℃, nitrogen for 2000h -1 The precursor solution was added to the 4Ni0.4Pd-SiO2 sample at a rate of 7ml / min under the conditions of purging and stirring at 40r / min, followed by oven treatment at 120℃ for 4 hours and calcination in a muffle furnace at 450℃ for 4 hours. Finally, the heterogeneous 20Ni5Cu3Pd / 4Ni0.4Pd-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400℃ for 500h. -1 The space velocity reduction activation was carried out for 4 hours.
[0082] Embodiment 14
[0083] Catalyst 14 is a non-uniform 20Ni5Co3Re / 4Ni2Co0.6Re-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 4.4 mm and a specific surface area of 410 m 2 / g, 0.5ml / g pore volume of Al2O3 beads as the carrier, prepare 80ml of aqueous solution containing 19.82g Ni(NO3)2·6H2O, 9.88g Co(NO3)2·6H2O, 0.86g NH4ReO4, use this aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 110℃ for 4 hours, and calcine it in a muffle furnace at 500℃ for 5 hours to obtain a uniform 4Ni2Co0.6Re-Al2O3 carrier. 2O3 sample; Step 2: Take the uniform 4Ni2Co0.6Re-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.7 ml. Prepare 75 ml of an aqueous solution containing 39.64 g Ni(NO3)2·6H2O, 7.41 g Co(NO3)2·6H2O, and 1.73 g NH4ReO4. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 110°C and nitrogen for 2000 h -1 The precursor solution was added to the 4Ni2Co0.6Re-Al2O3 sample at a rate of 5.2 ml / min under the conditions of purging and stirring at 38 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni5Co3Re / 4Ni2Co0.6Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0084] Embodiment 15
[0085] Catalyst 15 is a non-uniform 20Ni5Co3Re / 6Ni2.5Co0.85Re-Al2O3. Step 1: Weigh 100 g of 20Ni5Co3Re / 6Ni2.5Co0.85Re-Al2O3 with an average particle size of 4.4 mm and a specific surface area of 410 m 2 / g, 0.5ml / g pore volume of Al2O3 beads as the carrier, prepare 80ml of aqueous solution containing 29.73g Ni(NO3)2·6H2O, 12.35g Co(NO3)2·6H2O, 1.22g NH4ReO4, impregnate the above Al2O3 carrier with the aqueous solution, dry naturally, treat in an oven at 110℃ for 4 hours, and calcine in a muffle furnace at 500℃ for 5 hours to obtain a uniform 6Ni2.5Co0.85Re-A l2O3 sample; Step 2: Take the uniform 6Ni2.5Co0.85Re-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.7ml. Prepare 75ml of aqueous solution containing 34.68g Ni(NO3)2·6H2O, 6.17g Co(NO3)2·6H2O, and 1.55g NH4ReO4, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 110℃, nitrogen for 2000h -1The precursor solution was added to the 6Ni2.5Co0.85Re-Al2O3 sample at a rate of 5.2 ml / min under the conditions of purging and stirring at 38 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni5Co3Re / 6Ni2.5Co0.85Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0086] Example 16
[0087] Catalyst 16 is a non-uniform 10Co2Cu1.8B / 4Co0.6B-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.9 mm and a specific surface area of 380 m 2 / g, pore volume 0.4ml / g Al2O3 beads as the carrier, prepare 75ml of aqueous solution containing 19.76g Co(NO3)2·6H2O, 3.43g H3BO3, use the aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and roast it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 4Co0.6B-Al2O3 sample; Step 2: Take the uniform 4Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6ml, prepare 70ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 2.95g Cu(NO3)2, and 3.43g H3BO3, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 1500h -1 The precursor solution was added to the 4Co0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 10Co2Cu1.8B / 4Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 320°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0088] Embodiment 17
[0089] Catalyst 17 is a non-uniform 20Ni3Re / 4Ni0.6Re-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.9 mm and a specific surface area of 400 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 100ml of aqueous solution containing 19.82g Ni(NO3)2·6H2O, 0.86g NH4ReO4, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 110℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 4Ni0.6Re-SiO2 sample; Step 2: Take the uniform 4Ni0.6Re-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.8ml, prepare 90ml of aqueous solution containing 39.64g Ni(NO3)2·6H2O, 1.73g NH4ReO4, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 95℃, nitrogen for 1500h -1 The precursor solution was added to the 4Ni0.6Re-SiO2 sample at a rate of 5.2 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 450°C for 4 hours. Finally, a non-uniform 20Ni3Re / 4Ni0.6Re-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400°C for 800 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0090] Embodiment 18
[0091] Catalyst 18 is a non-uniform 20Ni10Co2.5Re2B / 3Ni1Co0.6B-Al2O3. Step 1: Weigh 100g of an average particle size of 3.9mm and a specific surface area of 380m 2 / g, 0.4ml / g pore volume of Al2O3 beads as carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 3.43g H3BO3, use the aqueous solution to impregnate the Al2O3 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6B-Al2O3 sample; Step 2: Take the uniform 3Ni1Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of aqueous solution containing 42.11 g Ni(NO3)2·6H2O, 22.22 g Co(NO3)2·6H2O, 1.80 g NH4ReO4, and 4.01 g H3BO3. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 1000 h. -1The precursor solution was added to the 3Ni1Co0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 20Ni10Co2.5Re2B / 3Ni1Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0092] Embodiment 19
[0093] Catalyst 19 is a non-uniform 30Ni20Co5.5Re2B / 3Ni1Co0.6Re-SiO2. Step 1: Weigh 100g of a catalyst with an average particle size of 3.9mm and a specific surface area of 400m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepared 100ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 0.86g NH4ReO4, impregnated the above SiO2 carrier with the aqueous solution, dried naturally, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6Re-SiO2 sample; Step 2: Take the uniform 3Ni1Co0.6Re-SiO2 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.8 ml. Prepare 140 ml of aqueous solution containing 66.89 g Ni(NO3)2·6H2O, 46.92 g Co(NO3)2·6H2O, 3.53 g NH4ReO4, and 5.72 g H3BO3. Divide the precursor solution into three equal parts and repeat the following process three times: heat at 100°C and nitrogen for 2000 h. -1 The precursor solution was added to the 3Ni1Co0.6Re-SiO2 sample at a rate of 5.5 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 450°C for 4 hours. Finally, a non-uniform 30Ni20Co5.5Re2B / 3Ni1Co0.6Re-SiO2 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 1000 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0094] Embodiment 20
[0095] Catalyst 20 is a non-uniform 60Ni20Co12Ru / 3Ni1Co0.6Ru-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.9 mm and a specific surface area of 380 m 2 / g, 0.4ml / g pore volume of Al2O3 beads as the carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 1.62g RuCl3·3H2O, use the aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and calcine it in a muffle furnace at 500℃ for 5 hours to obtain a uniform 3Ni1Co0.6Ru-Al2O 3 sample; Step 2: Take the uniform 3Ni1Co0.6Ru-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 220 ml of an aqueous solution containing 141.27 g Ni(NO3)2·6H2O, 46.92 g Co(NO3)2·6H2O, and 15.40 g RuCl3·3H2O, divide the precursor solution into four equal parts, and repeat the following process four times: heat at 100°C, nitrogen for 2000 h -1 The precursor solution was added to the 3Ni1Co0.6Ru-Al2O3 sample at a rate of 4.6 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 60Ni20Co12Ru / 3Ni1Co0.6Ru-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 400°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0096] Embodiment 21
[0097] Catalyst 21 is a non-uniform 20Ni5Cu3.75Pd / 4Cu0.6Pd-Al2O3. Step 1: Weigh 100g of an average particle size of 4.4mm and a specific surface area of 410m 2 / g, pore volume 0.5ml / g Al2O3 beads as carrier, prepare 80ml of aqueous solution containing 11.80g Cu(NO3)2, 1.46g Pd(NO3)2·2H2O, use this aqueous solution to impregnate the above Al2O3 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 500℃ for 5 hours to obtain a uniform 4Cu0.6Pd-Al2O3 sample; Step 2: Take the uniform 4Cu0.6Pd-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.7ml, prepare 75ml of aqueous solution containing 49.55g Ni(NO3)2·6H2O, 1.48g Cu(NO3)2, and 3.84g Pd(NO3)2·2H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 105℃, nitrogen for 2000h -1The precursor solution was added to the 4Cu0.6Pd-Al2O3 sample at a rate of 5 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni5Cu3.75Pd / 4Cu0.6Pd-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0098] Embodiment 22
[0099] Catalyst 22 is a non-uniform 20Ni5Co3Re / 4Co0.48Re-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 4.4 mm and a specific surface area of 410 m 2 / g, pore volume 0.5ml / g Al2O3 beads are used as carriers, 80ml of aqueous solution containing 19.76g Co(NO3)2·6H2O and 0.69g NH4ReO4 is prepared, the Al2O3 carrier is impregnated with the aqueous solution, dried naturally, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 500℃ for 5 hours to obtain a uniform 4Co0.48Re-Al2O3 sample; Step 2: Take the uniform 4Co0.48Re-Al2O3 sample prepared in the first step, and the water absorption per gram of the sample is measured to be 0.7ml, and 75ml of aqueous solution containing 49.55g Ni(NO3)2·6H2O, 2.47g Co(NO3)2·6H2O, and 1.81g NH4ReO4 is prepared, the precursor liquid is divided into two equal parts, and the following process is repeated twice: heating at 105℃, nitrogen for 1500h -1 The precursor solution was added to the 4Co0.48Re-Al2O3 sample at a rate of 4.8 ml / min under the conditions of purging and stirring at 35 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni5Co3Re / 4Co0.48Re-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 450°C for 500 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0100] Comparative Example 1
[0101] Catalyst 23 is a uniform 4.5Co0.2Pd0.25Re-SiO2. Weigh 100 g of the catalyst with an average particle size of 3.9 mm and a specific surface area of 400 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 100ml aqueous solution containing 22.22g Co(NO3)2·6H2O, 0.49g Pd(NO3)2·2H2O, 0.36g NH4ReO4, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in a 110℃ oven for 4 hours, and calcine in a 400℃ muffle furnace for 5 hours to obtain a uniform 4.5Co0.2Pd0.25Re-SiO2 catalyst. Before use, in 400℃ hydrogen, 600h -1 The space velocity reduction activation was carried out for 4 hours.
[0102] Comparative Example 2
[0103] Catalyst 24 is a uniform type 25Co2Pd1.75Re-SiO2. Weigh 100 g of the catalyst with an average particle size of 3.9 mm and a specific surface area of 400 m 2 / g, 0.5ml / g pore volume of SiO2 beads as the carrier, prepare 200ml of aqueous solution containing 123.47g Co(NO3)2·6H2O, 4.89g Pd(NO3)2·2H2O, 2.52g NH4ReO4, divide the above precursor liquid into two equal parts, repeat the following preparation process twice: the precursor liquid is impregnated with the above SiO2 carrier, naturally dried, treated in an oven at 110℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 25Co2Pd1.75Re-SiO2 catalyst. Before use, in hydrogen at 400℃ for 800h -1 The space velocity reduction activation was carried out for 6 hours.
[0104] Comparative Example 3
[0105] Catalyst 25 is eggshell type 25Co2Pd1.75Re-SiO2. Weigh 100g of the average particle size of 3.9mm and the specific surface area of 400m 2 / g, 0.5ml / g pore volume of SiO2 beads as the carrier, the water absorption of each gram of sample was measured to be 1ml, 110ml of aqueous solution containing 61.74g Co(NO3)2·6H2O, 2.44g Pd(NO3)2·2H2O, 1.26g NH4ReO4 was prepared, the precursor solution was divided into two equal parts, and the following process was repeated twice: heating at 100℃, nitrogen for 1500h -1 The precursor solution was added to the SiO2 pellets at a rate of 5 ml / min under the conditions of purging and stirring at 38 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 450°C for 4 hours. The eggshell-type 25Co2Pd1.75Re-SiO2 catalyst was finally obtained. Before use, the catalyst was heated in hydrogen at 400°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0106] Comparative Example 4
[0107] Catalysts 23 and 25 were mixed in a volume ratio of 1:1. Before use, they were heated in hydrogen at 400 °C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0108] Comparative Example 5
[0109] Catalyst 26 is a uniform 4.5Co0.2Pd0.25Re-SiO2. Weigh 100 g of a catalyst with an average particle size of 1.5 mm and a specific surface area of 410 m 2 / g, and a pore volume of 0.6ml / g SiO2 beads were used as a carrier, and 110ml of an aqueous solution containing 22.22g Co(NO3)2·6H2O, 0.49g Pd(NO3)2·2H2O, and 0.36g NH4ReO4 was prepared. The SiO2 carrier was impregnated with the aqueous solution, naturally dried, treated in an oven at 110°C for 4 hours, and calcined in a muffle furnace at 400°C for 5 hours to obtain a uniform 4.5Co0.2Pd0.25Re-SiO2 catalyst.
[0110] Catalysts 26 and 25 were mixed in a volume ratio of 1:1. Before use, they were heated in hydrogen at 400 °C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0111] Comparative Example 6
[0112] Catalyst 27 is a non-uniform 2.5Re2B / 0.6B-Al2O3 without adding active metal. Step 1: Weigh 100g of an average particle size of 3.9mm and a specific surface area of 380m 2 / g, pore volume 0.4ml / g Al2O3 beads as carrier, prepare 75ml of aqueous solution containing 3.43g H3BO3, use this aqueous solution to impregnate the above Al2O3 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and roast in a muffle furnace at 400℃ for 5 hours to obtain a uniform 0.6B-Al2O3 sample; Step 2: Take the uniform 0.6B-Al2O3 sample prepared in the first step, and measure the water absorption per gram of the sample to be 0.6ml, prepare 70ml of aqueous solution containing 1.80g NH4ReO4 and 4.01g H3BO3, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 1000h -1 The precursor solution was added to the 0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 2.5Re2B / 0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0113] Comparative Example 7
[0114] Catalyst 28 is a non-uniform 20Ni10Co / 3Ni1Co-Al2O3 without any additive element. Step 1: Weigh 100 g of 3.9 mm average particle size and 380 m2 specific surface area. 2 / g, pore volume 0.4ml / g Al2O3 beads as carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, use this aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and roast it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co-Al2O3 sample; Step 2: Take the uniform 3Ni1Co-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6ml, prepare 70ml of aqueous solution containing 42.11g Ni(NO3)2·6H2O, 22.22g Co(NO3)2·6H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 90℃, nitrogen for 1000h -1 The precursor solution was added to the 3Ni1Co-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 20Ni10Co / 3Ni1Co-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0115] Comparative Example 8
[0116] Catalyst 29 is a non-uniform 20Ni10Co0.2Re0.6B / 3Ni1Co0.6B-Al2O3. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.9 mm and a specific surface area of 380 m 2 / g, 0.4ml / g pore volume of Al2O3 beads as the carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 3.43g H3BO3, use this aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and calcine it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6B-Al2 O3 sample; Step 2: Take the uniform 3Ni1Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of an aqueous solution containing 42.11 g Ni(NO3)2·6H2O, 22.22 g Co(NO3)2·6H2O, and 0.14 g NH4ReO4. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 1000 h -1The precursor solution was added to the 3Ni1Co0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni10Co0.2Re0.6B / 3Ni1Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0117] Comparative Example 9
[0118] Catalyst 30 is a non-uniform 20Ni10Co6Re6B / 3Ni1Co0.6B-Al2O3. Step 1: Weigh 100g of an average particle size of 3.9mm and a specific surface area of 380m 2 / g, pore volume 0.4ml / g Al2O3 beads were used as carriers, 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, and 3.43g H3BO3 was prepared, the Al2O3 carrier was impregnated with the aqueous solution, naturally dried, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6B-Al2O3 sample; Step 2: Take the uniform 3Ni1Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of aqueous solution containing 42.11 g Ni(NO3)2·6H2O, 22.22 g Co(NO3)2·6H2O, 4.32 g NH4ReO4, and 15.46 g H3BO3. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 1000 h. -1 The precursor solution was added to the 3Ni1Co0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni10Co6Re6B / 3Ni1Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0119] Comparative Example 10
[0120] Catalyst 31 is a non-uniform 6Ni2Co0.2Re0.6B / 3Ni1Co0.6B-Al2O3. Step 1: Weigh 100g of 6Ni2Co0.2Re0.6B / 3Ni1Co0.6B-Al2O3 with an average particle size of 3.9mm and a specific surface area of 380m 2 / g, 0.4ml / g pore volume of Al2O3 beads as the carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 3.43g H3BO3, use the aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and calcine it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6B-Al 2O3 sample; Step 2: Take the uniform 3Ni1Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of an aqueous solution containing 7.43 g Ni(NO3)2·6H2O, 2.47 g Co(NO3)2·6H2O, and 0.14 g NH4ReO4, divide the precursor solution into two equal parts, and repeat the following process twice: heat at 90°C and nitrogen for 1000 h -1 The precursor solution was added to the 3Ni1Co0.6B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 6Ni2Co0.2Re0.6B / 3Ni1Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0121] Comparative Example 11
[0122] Catalyst 32 is a non-uniform 60Ni40Co6Re4B / 3Ni1Co0.6B-Al2O3. Step 1: Weigh 100g of 3.9mm average particle size and 380m3 specific surface area. 2 / g, pore volume 0.4ml / g Al2O3 beads were used as carriers, 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, and 3.43g H3BO3 was prepared, the Al2O3 carrier was impregnated with the aqueous solution, naturally dried, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.6B-Al2O3 sample; Step 2: Take the uniform 3Ni1Co0.6B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 280 ml of aqueous solution containing 141.21 grams of Ni(NO3)2·6H2O, 96.31 grams of Co(NO3)2·6H2O, 4.32 grams of NH4ReO4, and 9.73 grams of H3BO3. Divide the precursor liquid into eight equal parts and repeat the following process eight times: heat at 100°C and nitrogen for 800 hours. -1The precursor solution was added to the 3Ni1Co0.6B-Al2O3 sample at a rate of 4.2 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 60Ni40Co6Re4B / 3Ni1Co0.6B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 1000 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0123] Comparative Example 12
[0124] Catalyst 33 is a non-uniform 20Ni10Co2.5Re2B / 3Ni1Co0.02B-Al2O3. Step 1: Weigh 100g of a catalyst with an average particle size of 3.9mm and a specific surface area of 380m 2 / g, 0.4ml / g pore volume of Al2O3 beads as carrier, prepare 75ml of aqueous solution containing 14.86g Ni(NO3)2·6H2O, 4.94g Co(NO3)2·6H2O, 0.11g H3BO3, use the aqueous solution to impregnate the Al2O3 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Ni1Co0.02B-Al2O3 sample; Step 2: Take the uniform 3Ni1Co0.02B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of aqueous solution containing 42.11 g Ni(NO3)2·6H2O, 22.22 g Co(NO3)2·6H2O, 1.80 g NH4ReO4, and 5.67 g H3BO3. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 1000 h. -1 The precursor solution was added to the 3Ni1Co0.02B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, the heterogeneous 20Ni10Co2.5Re2B / 3Ni1Co0.02B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0125] Comparative Example 13
[0126] Catalyst 34 is a non-uniform 20Ni10Co2.5Re2B / 8Ni4Co1.8B-Al2O3. Step 1: Weigh 100g of an average particle size of 3.9mm and a specific surface area of 380m 2 / g, pore volume 0.4ml / g Al2O3 beads as the carrier, prepare 75ml of aqueous solution containing 39.64g Ni(NO3)2·6H2O, 19.76g Co(NO3)2·6H2O, 10.30g H3BO3, use this aqueous solution to impregnate the above Al2O3 carrier, dry it naturally, treat it in a 120℃ oven for 4 hours, and calcine it in a 400℃ muffle furnace for 5 hours to obtain a uniform 8Ni4Co1.8B-Al2O3 sample Step 2: Take the uniform 8Ni4Co1.8B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 70 ml of an aqueous solution containing 29.73 g Ni(NO3)2·6H2O, 14.82 g Co(NO3)2·6H2O, 1.80 g NH4ReO4, and 0.57 g H3BO3. Divide the precursor solution into two equal parts and repeat the following process twice: heat at 90°C and nitrogen for 1000 h. -1 The precursor solution was added to the 8Ni4Co1.8B-Al2O3 sample at a rate of 4 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 20Ni10Co2.5Re2B / 8Ni4Co1.8B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0127] Comparative Example 14
[0128] Catalyst 35 is a non-uniform 20Ni10Co2.5Re2B / 0.3Ni0.2Co0.08B-Al2O3. Step 1: Weigh 100g of a catalyst with an average particle size of 3.9mm and a specific surface area of 380m 2 / g, pore volume 0.4ml / g Al2O3 beads were used as carriers, 75ml of aqueous solution containing 1.48g Ni(NO3)2·6H2O, 0.99g Co(NO3)2·6H2O, and 0.46g H3BO3 was prepared, the Al2O3 carrier was impregnated with the aqueous solution, naturally dried, treated in an oven at 120℃ for 4 hours, and calcined in a muffle furnace at 400℃ for 5 hours to obtain a uniform 0.3Ni0.2Co0.08B-Al2O3 sample; Step 2: Take the uniform 0.3Ni0.2Co0.08B-Al2O3 sample prepared in the first step, and measure the water absorption of each gram of sample to be 0.6 ml. Prepare 110 ml of aqueous solution containing 48.80 g Ni(NO3)2·6H2O, 24.20 g Co(NO3)2·6H2O, 1.80 g NH4ReO4, and 5.50 g H3BO3. Divide the precursor solution into three equal parts and repeat the following process three times: heat at 95°C and nitrogen for 1000 h. -1The precursor solution was added to the 0.3Ni0.2Co0.08B-Al2O3 sample at a rate of 4.2 ml / min under the conditions of purging and stirring at 30 r / min, followed by oven treatment at 120°C for 4 hours and calcination in a muffle furnace at 500°C for 4 hours. Finally, a non-uniform 20Ni10Co2.5Re2B / 0.3Ni0.2Co0.08B-Al2O3 catalyst was obtained. Before use, the catalyst was heated in hydrogen at 420°C for 600 h. -1 The space velocity reduction activation was carried out for 4 hours.
[0129] Comparative Example 15
[0130] Catalyst 36 is a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 0.4 mm and a specific surface area of 450 m 2 / g, pore volume 0.6ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ru-SiO2 sample; Step 2: Take the uniform 3Co0.3Ru-SiO2 sample prepared in the first step, measure the water absorption per gram of sample to be 1.1ml, prepare 70ml of aqueous solution containing 59.76g Co(NO3)2·6H2O, 5.13g RuCl3·3H2O, heat at 120℃, nitrogen for 2500h -1 The precursor solution was added to the 3Co0.3Ru-SiO2 sample at a rate of 4.2 ml / min under the conditions of purging and stirring at 50 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0131] Comparative Example 16
[0132] Catalyst 37 is a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 10.3 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ru-SiO2 sample; Step 2: Take the uniform 3Co0.3Ru-SiO2 sample prepared in the first step, measure the water absorption per gram of the sample to be 1.1ml, prepare 70ml of aqueous solution containing 59.76g Co(NO3)2·6H2O, 5.13g RuCl3·3H2O, heat at 80℃, nitrogen for 1500h -1 The precursor solution was added to the 3Co0.3Ru-SiO2 sample at a rate of 4.2 ml / min under the conditions of purging and stirring at 30 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0133] Comparative Example 17
[0134] Catalyst 38 is a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 22 mm and a specific surface area of 470 m 2 / g, pore volume 0.6ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ru-SiO2 sample; Step 2: Take the uniform 3Co0.3Ru-SiO2 sample prepared in the first step, measure the water absorption of each gram of sample to be 1ml, prepare 18ml of aqueous solution containing 8.69g Co(NO3)2·6H2O, 0.75g RuCl3·3H2O, divide the precursor liquid into two equal parts, and repeat the following process twice: heat at 120℃, nitrogen for 2500h -1 The precursor solution was added to the 3Co0.3Ru-SiO2 sample at a rate of 1 ml / min under the conditions of purging and stirring at 40 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0135] Comparative Example 18
[0136] Catalyst 39 is a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 1.1 mm and a specific surface area of 450 m 2 / g, pore volume 0.6ml / g SiO2 SiO2 beads as the carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.81g RuCl3·3H2O, use the aqueous solution to impregnate the above SiO2 carrier, dry it naturally, treat it in an oven at 120℃ for 4 hours, and roast it in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ru-SiO2 sample; Step 2: Take the uniform 3Co0.3Ru-SiO2 sample prepared in the first step, measure the water absorption of each gram of sample to be 1ml, prepare 110ml of aqueous solution containing 97.79g Co(NO3)2·6H2O, 8.39g RuCl3·3H2O, heat it at 80℃ and nitrogen for 2000h -1 The precursor solution was added to the 3Co0.3Ru-SiO2 sample at a rate of 5.5 ml / min under the conditions of purging and stirring at 35 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ru / 3Co0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0137] Comparative Example 19
[0138] Catalyst 40 is a non-uniform 25Fe3.75Ru / 3Fe0.3Ru-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 12.99g Fe(NO3)2, 0.81g RuCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and roast in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Fe0.3Ru-SiO2 sample; Step 2: Take the uniform 3Fe0.3Ru-SiO2 sample prepared in the first step, measure the water absorption per gram of the sample to be 1.1ml, prepare 80ml of aqueous solution containing 52.41g Fe(NO3)2·6H2O, 5.13g RuCl3·3H2O, heat at 100℃, nitrogen for 2500h -1The precursor solution was added to the 3Fe0.3Ru-SiO2 sample at a rate of 3.5 ml / min under the conditions of purging and stirring at 35 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Fe3.75Ru / 3Fe0.3Ru-SiO2 catalyst. Before use, it was heated in hydrogen at 400°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0139] Comparative Example 20
[0140] Catalyst 41 is a non-uniform 25Co3.75Ir / 3Co0.3Ir-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 14.82g Co(NO3)2·6H2O, 0.55g IrCl3·3H2O, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and calcine in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Co0.3Ir-SiO2 sample; Step 2: Take the uniform 3Co0.3Ir-SiO2 sample prepared in the first step, measure the water absorption per gram of the sample to be 1.1ml, prepare 80ml of aqueous solution containing 59.76g Co(NO3)2·6H2O, 3.48g IrCl3·3H2O, heat at 100℃, nitrogen for 2500h -1 The precursor solution was added to the 3Co0.3Ir-SiO2 sample at a rate of 3.5 ml / min under the conditions of purging and stirring at 35 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Co3.75Ir / 3Co0.3Ir-SiO2 catalyst. Before use, it was heated in hydrogen at 320°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0141] Comparative Example 21
[0142] Catalyst 42 is a non-uniform 25Fe3.75Cr / 3Fe0.3Cr-SiO2. Step 1: Weigh 100 g of a catalyst with an average particle size of 3.4 mm and a specific surface area of 460 m 2 / g, pore volume 0.5ml / g SiO2 beads as carrier, prepare 120ml of aqueous solution containing 12.99g Fe(NO3)2, 1.37g Cr(NO3)3, use this aqueous solution to impregnate the above SiO2 carrier, dry naturally, treat in an oven at 120℃ for 4 hours, and roast in a muffle furnace at 400℃ for 5 hours to obtain a uniform 3Fe0.3Cr-SiO2 sample; Step 2: Take the uniform 3Fe0.3Cr-SiO2 sample prepared in the first step, and measure the water absorption per gram of the sample to be 1.1ml, prepare 80ml of aqueous solution containing 52.41g Fe(NO3)2·6H2O, 8.68g Cr(NO3)3, heat at 100℃, nitrogen for 2500h -1 The precursor solution was added to the 3Fe0.3Cr-SiO2 sample at a rate of 3.5 ml / min under the conditions of purging and stirring at 35 r / min. Then, it was treated in an oven at 120°C for 4 hours and calcined in a muffle furnace at 500°C for 5 hours to obtain a non-uniform 25Fe3.75Cr / 3Fe0.3Cr-SiO2 catalyst. Before use, it was heated in hydrogen at 400°C for 800 h. -1 The space velocity reduction activation was carried out for 5 hours.
[0143] Comparative Example 22
[0144] Catalyst 43 is a commercial Raney nickel catalyst.
[0145]
[0146]
[0147] In summary, it can be seen from the results of Examples 1-5 that as the thickness of the catalyst outer layer increases from 0.15 to 0.9 mm, the catalyst activity increases accordingly, but too large an outer layer thickness will lead to an increase in the selectivity of oligomers, thereby causing the selectivity of hexamethylenediamine to decrease; combined with the results of Comparative Examples 1, 2, 15 and 16, it can be seen that when the outer layer thickness is 0.05 mm (too small) or the active metal loading of the uniform catalyst is 4.5% (too low), the conversion rate of 1,6-hexanediol is low, and there is a lot of 6-amino-1-hexanol in the product; when the outer layer thickness is 1.2 mm (too large) or a uniform catalyst is used, a large amount of oligomers are generated in the product, and the activity is reduced instead. This is because a large amount of oligomers cover the catalyst surface and inhibit the reaction. It can be seen from Examples 6-10 that as the volume of the outer layer increases from 23% to 80% of the total catalyst volume, the catalytic activity increases accordingly, but the increase in the volume of the outer layer tends to increase the selectivity of oligomers; combined with Comparative Examples 17 and 18, it can be seen that the outer layer volume accounts for 8% (too small) will lead to reduced catalytic activity, and the outer layer volume accounts for 90% (too large) will lead to an increase in oligomers. It can be seen from Examples 11-15 that as the amount of active metal in the inner core increases from 1.2 to 8.5%, the conversion rate of 1,6-hexanediol gradually increases, but the selectivity of oligomers also shows an increasing trend; combined with Comparative Examples 3, 13 and 14, it can be seen that when the amount of active metal in the inner core is 12% (too much), a large amount of oligomers will be generated, while the catalytic activity is low on eggshell catalysts with an inner core active metal amount of 0.5% (too little) or only in the outer layer. It can be seen from Examples 16-20 that when the amount of active metal in the outer layer is 12-20%, the catalytic activity is low, and when the amount of active metal in the outer layer is 80%, the generation of a large amount of oligomers will inhibit the conversion of 1,6-hexanediol, resulting in a decrease in conversion rate; combined with Comparative Examples 10 and 11, it can be seen that selecting an appropriate amount of active metal in the outer layer is the key to improving catalytic activity and inhibiting the generation of oligomers. It can be seen from Examples 21-22 that the heterogeneous catalyst of the present invention is also suitable for the hydroamination reaction of a mixture of 1,6-hexanediol or 6-amino-1-hexanol. It can be seen from Examples 8 and 21 that the catalyst of the present invention has excellent stability in the 1000h life evaluation; combined with Comparative Examples 7, 12, 21 and 22, it can be seen that when a traditional Raney nickel catalyst is used or no additives are added to the inner core and outer layer or the amount of the inner core additive is too small or other additives other than those specified in this patent are added to the inner core and outer layer, it is easy to cause a decrease in catalytic life. Comparative Examples 4 and 5 show that the effect of the heterogeneous catalyst of the present invention cannot be obtained by physically mixing the eggshell catalyst and the uniform low-load catalyst or reducing the particle size of the uniform catalyst. The above results prove that the heterogeneous catalyst described in the present application has the effects of reducing oligomer formation, increasing catalyst life, and increasing the yield of hexamethylenediamine.
Claims
1. A method for preparing 1,6-hexanediamine, characterized in that: Using 1,6-hexanediol as a raw material, the target product 1,6-hexanediamine is produced by hydroamination under the action of a heterogeneous catalyst; The catalyst particles of the heterogeneous catalyst are composed of an inner core and an outer layer, wherein the inner core is the inner center part of the catalyst particle, and the outer layer is the part from the inner core of the catalyst particle to the outer surface of the particle; The inner core and outer layer of the catalyst particles are composed of active metals, additives and carriers; The carrier is one or a combination of granular SiO2 or Al2O3; the inner core active metal and the auxiliary agent are loaded inside the carrier particles as the inner core of the catalyst, and the outer layer active metal and the auxiliary agent are loaded in the area between the outer surface of the carrier particles and the inner core as the outer layer of the catalyst; the inner core and outer layer active metal and auxiliary agent components are uniformly dispersed on the inner surface of the inner core and outer layer pores of the carrier respectively; The particle size of the granular carrier is 0.4-50 mm; the thickness of the outer layer of the heterogeneous catalyst is 0.1-1 mm; The active metal element is one or a combination of two or more of Co, Ni, and Cu, wherein the mass of the inner core active metal accounts for 1-9% of the mass of the inner core carrier; the mass of the outer layer active metal accounts for 10-95% of the mass of the outer layer carrier; The auxiliary agent component is one or a combination of two or more of Ru, Pd, Fe, B, Zn, Re, W, and Y, wherein the mass ratio of the inner core auxiliary agent to the inner core active metal is 0.01-0.3:1; the mass ratio of the outer layer auxiliary agent to the outer layer active metal is 0.05-0.3:
1.
2. The method according to claim 1, characterized in that: The particle size of the granular carrier is 1.2-14 mm; the thickness of the outer layer of the heterogeneous catalyst is 0.2-0.8 mm; The active metal element is one or a combination of two or more of Co, Ni, and Cu, wherein the mass of the inner core active metal accounts for 1.5-7% of the mass of the inner core carrier; the mass of the outer layer active metal accounts for 15-60% of the mass of the outer layer carrier; The auxiliary agent component is one or a combination of two or more of Ru, Pd, Re, and W, wherein the mass ratio of the inner core auxiliary agent to the inner core active metal is 0.05-0.2:1; the mass ratio of the outer layer auxiliary agent to the outer layer active metal is 0.1-0.2:
1.
3. The method according to claim 2, characterized in that: The particle size of the granular carrier is 2.5-7.5 mm; the thickness of the outer layer of the heterogeneous catalyst is 0.3-0.6 mm; The active metal element is one or a combination of two or more of Co, Ni, and Cu, wherein the mass of the inner core active metal accounts for 2-4.5% of the mass of the inner core carrier; the mass of the outer layer active metal accounts for 25-45% of the mass of the outer layer carrier.
4. The method according to claim 1, characterized in that: The active metal loaded on the inner core is A, and the mass of A loaded per unit volume is M, the auxiliary agent is B, and the mass of B loaded per unit volume is N; the active metal loaded on the outer layer includes A, and the mass of A loaded per unit volume is greater than or equal to M, the auxiliary agent includes B, and the mass of B loaded per unit volume is greater than or equal to N; and the mass of the total active metal loaded per unit volume on the outer layer is greater than the mass of the total active metal loaded per unit volume on the inner core, and the mass of the total auxiliary agent loaded per unit volume on the outer layer is greater than or equal to the mass of the total auxiliary agent loaded per unit volume on the inner core; The ratio of the outer layer volume of the heterogeneous catalyst to the total catalyst volume is 10-88%; The granular carrier is one or more of the following shapes: cylindrical, annular, spherical, trilobal, quadrilobal, and amorphous; The specific surface area of the granular carrier is 50-2000m 2 / g; pore volume is 0.05~2.0ml / g.
5. The method according to claim 4, characterized in that: The ratio of the outer layer volume of the heterogeneous catalyst to the total catalyst volume is 30-75%; The specific surface area of the granular carrier is 150-600m 2 / g; pore volume is 0.4~1.2ml / g.
6. The method according to claim 5, characterized in that: The ratio of the outer layer volume of the heterogeneous catalyst to the total catalyst volume is 40-65%.
7. The method according to claim 1, characterized in that: The synthesis of the heterogeneous catalyst adopts a two-step method: A. The first step is to prepare a precursor solution of an active metal or an additive, load the active metal and the additive onto a carrier by an impregnation method or a precipitation method, and obtain a uniform catalyst after drying and calcination, wherein the loading amount of the active metal and the additive on the obtained uniform catalyst is the same as the loading amount required for the inner core of the heterogeneous catalyst; The second step is to prepare the precursor liquid of active metal and auxiliary agent on the uniform catalyst prepared in the first step according to the required loading amount of the outer layer, load the active metal and auxiliary agent to the outer layer of the uniform catalyst by competitive adsorption method, air bag retardation method or rapid drying method, and finally obtain the heterogeneous catalyst after drying and calcination; Or, B. the two-step method changes the order of the first step and the second step according to actual needs; Specifically, the first step is to prepare the precursor liquid of active metal and additive according to the volume ratio of the outer layer of the heterogeneous catalyst and the difference in the loading amount of active metal and additive between the outer layer and the inner core, and load the active metal and additive to the outer layer of the carrier by competitive adsorption method, air bag retardation method or rapid drying method, and finally obtain the eggshell catalyst after drying and calcination; The second step is to prepare a precursor liquid on the eggshell catalyst prepared in the first step according to the active metal and auxiliary agent loading amount required by the inner core, load the active metal and auxiliary agent onto the eggshell catalyst by an impregnation method or a precipitation method, and obtain a heterogeneous catalyst after drying and calcination; The calcination temperature is 200-800° C., the time is 0.5-15 hours, and the calcination is carried out in an atmosphere of one or both of air and oxygen.
8. The method according to claims 1-7, characterized in that: The preparation process of the rapid drying method is as follows: according to the proportion of the required non-uniform catalyst outer layer to the total catalyst volume, the loading amount of the outer layer active metal and the auxiliary agent, and the water absorption rate of the uniform catalyst or the carrier, the precursor liquid is prepared, and the precursor liquid is dripped onto the uniform catalyst or the carrier, and then dried and calcined to obtain the non-uniform catalyst or the eggshell catalyst; wherein, during the process of dripping the precursor liquid, heating, atmosphere purging and stirring are maintained, the dripping time is 0.1-2h, the heating temperature is 50-200°C, the atmosphere is one or two of air and nitrogen, and the purge air velocity is 100-10000h -1 , the stirring speed is 10~300r / min; the volume of the prepared precursor liquid is 1~2.2 times the product of the volume proportion of the outer layer of the catalyst and the saturated water absorption of the uniform catalyst or the carrier.
9. The method according to claim 1, characterized in that: The reactor for producing the target product 1,6-hexanediamine by hydroamination of 1,6-hexanediol as a raw material under the action of a heterogeneous catalyst is a fixed bed, a fluidized bed, a slurry bed, a bubbling bed or a reactor; the pressure is 2-25 MPa; the reaction temperature is 80-240°C.
10. The method according to claim 9, wherein: The reactor for producing the target product 1,6-hexanediamine by hydroamination of 1,6-hexanediol as a raw material under the action of a heterogeneous catalyst is a fixed bed, a fluidized bed, a slurry bed, a bubbling bed or a reactor; the pressure is 4-18 MPa; the reaction temperature is 120-180°C.
11. The method according to claim 1 or 9, characterized in that: The molar fraction of hydrogen is 0.5-20% of the total feed, and the total feed includes reaction raw materials and hydrogen; the reaction raw materials are ammonia and 1,6-hexanediol, or 6-amino-1-hexanol, or a 1,6-hexanediol / 6-amino-1-hexanol mixture with a mass ratio of 1: (0.01-100), or a 1,6-hexanediol / 6-amino-1-hexanol / cyclohexylimine mixture with a mass ratio of 1: (0.01-100): (0.1-10), or a 6-amino-1-hexanol / cyclohexylimine mixture with a mass ratio of 1: (0.2-8), wherein the ratio of the total mole number of 1,6-hexanediol or 6-amino-1-hexanol or cyclohexylimine to the mole number of ammonia is 1: 1-60; the liquid hourly space velocity of the reaction raw materials other than ammonia is 0.05-4h -1 .
12. The method according to claim 11, characterized in that: The ratio of the total mole number of 1,6-hexanediol or 6-amino-1-hexanol or cyclohexylimine to the mole number of ammonia is 1:6~30; the liquid hourly space velocity of the reaction raw materials other than ammonia is 0.2~2h -1 .
13. The method according to claims 1-7, characterized in that: The heterogeneous catalyst needs to be reduced and activated before use. The reduction and activation treatment is carried out in a hydrogen atmosphere. The activation conditions are: temperature 150-700°C, time 0.5-12h, hydrogen space velocity 20-4000h -1 .
Citation Information
Patent Citations
Manufacture of aliphatic diamines
US2754330A
Process for the preparation of alkylene diamines
US3215742A
Catalyst for synthesizing hexamethylenediamine
CN106807377A
Catalyst used for synthesis of hexanediamine
CN106807395A